Unearthing Agricultural Land Use Dynamics in Indonesia: Between Food Security and Policy Interventions - Uly Faoziyah; Muhammad Faruk Rosyaridho; Romauli Panggabean (Land)
Despite its essential and irreplaceable role in food security, the agricultural sector is often perceived as having the potential to be sacrificed in the name of economic growth, leading to significant land cover transformation into built-up areas and plantations. This complexity prompts critical questions regarding the efficacy of agricultural policy interventions, including augmenting production capacity, diversifying commodities, and expanding agricultural land in light of Indonesia Emas 2045, which embodies Indonesia’s ambitious multidimensional developmental transformation. This study employed a system dynamic approach with region-based closed feedback, focusing on four primary commodities: rice, cassava, corn, and palm oil. It concludes that food vulnerability will become increasingly severe by 2045, particularly in Java Island, which, despite being the sole area with a food surplus, is also experiencing escalating development pressures. In other regions, this pressure transforms transitory land from areas growing rice to areas growing other agricultural commodities, and subsequently to built-up land. The policy intervention scenario, albeit less impactful in reflecting substantial land cover changes nationally, can facilitate swift commodity production. This study emphasizes the necessity of intensifying rather than expanding agricultural land.